2015
DOI: 10.1155/2016/7653489
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes and Their Therapeutic Potentials of Stem Cells

Abstract: Exosomes, a group of vesicles originating from the multivesicular bodies (MVBs), are released into the extracellular space when MVBs fuse with the plasma membrane. Numerous studies indicate that exosomes play important roles in cell-to-cell communication, and exosomes from specific cell types and conditions display multiple functions such as exerting positive effects on regeneration in many tissues. It is widely accepted that the therapeutic potential of stem cells may be mediated largely by the paracrine fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
156
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 191 publications
(162 citation statements)
references
References 125 publications
2
156
0
4
Order By: Relevance
“…90 MSC-DEs have low immunogenicity capacity rather than MSCs 66, 91 and have no infection risks. In addition, there is the risk of ectopic differentiation of MSCs after systemic infusion; 92 hence, exosome-based therapy can be a good replacement for mesenchymal stem cell-based therapy soon.…”
Section: Discussionmentioning
confidence: 99%
“…90 MSC-DEs have low immunogenicity capacity rather than MSCs 66, 91 and have no infection risks. In addition, there is the risk of ectopic differentiation of MSCs after systemic infusion; 92 hence, exosome-based therapy can be a good replacement for mesenchymal stem cell-based therapy soon.…”
Section: Discussionmentioning
confidence: 99%
“…3). Clinical and animal studies demonstrated the efficacy of MSC therapies and the importance of MSC paracrine secretion in various diseases [27,28]. Cosenza et al injected MSC-derived exosomes into a collagenase-induced OA model and found that it protected mice from joint damage [29].…”
Section: Therapeutic Potential Of Exosomes In Joint Diseasesmentioning
confidence: 99%
“…2, 3). Studies suggest that the therapeutic effect of stem cells largely depends on their paracrine actions [27,28]. Exosomes secreted from stem cells carry critical, biologically active contents that have disease intervention potential [46,47].…”
Section: Emerging Roles Of Exosomes In Joint Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…These MVBs fuse with the plasma membrane releasing intraluminal vesicles into the extracellular matrix in the form of exosomes (163-165). They are present as extracellular space as vesicles (163). The diameter of exosome range from 30-120 nm.…”
Section: Role Of Mirna Containing Exosomes In Cardiac Regenerationmentioning
confidence: 99%